PxDorsal Regulates the Expression of Antimicrobial Peptides and Affects the Bt Susceptibility of Plutella xylostella - Yan Sun; Haoqi Wen; Wenrui Xue; Xiaofeng Xia (Insects)
The insect NF-κB pathway is primarily constituted by nuclear factor κB (NF-κB) and the inhibitor of κB (IκB), which plays a crucial role in the innate immune response. Dorsal and Cactus, as NF-κB and IκB factors, are important downstream regulators of the Toll pathway in Plutella xylostella. In this study, the PxDorsal and PxCactus genes of P. xylostella were cloned, and the molecular docking demonstrated that PxDorsal and PxCactus can interact with each other. RT-qPCR results indicated that PxDorsal and PxCactus were expressed in all stages, and the expression of PxDorsal, PxCactus, and antimicrobial peptides PxGloverin2, PxMoricin3, and PxLysozyme2 were significantly down-regulated under Bacillus thuringiensis (Bt8010) infection. Interestingly, silencing the PxDorsal gene by RNA interference (RNAi) significantly down-regulated the expression of PxGloverin2 and PxMoricin3 and increased the epidermis melanization of P. xylostella larvae fed with Bt8010. Our findings indicate that PxDorsal and PxCactus may interact with each other, and silencing PxDorsal inhibits the expression of downstream antimicrobial peptides, thereby enhance the susceptibility of P. xylostella to Bt8010. This study contributes a theoretical basis for further research on the Toll pathway of P. xylostella to pathogens and offers insights for screening effective biological control targets from the perspective of the immune system.